HALAL INDUSTRY DEVELOPMENT STRATEGIES: Muslims’ Responses and Sharia Compliance in Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
Halal Industries have persistently become an important issue globally, including in Indonesia. This study aims to analyze the strategies for halal industry development implemented by business actors in Indonesia as well as provide Indonesian Muslim’s responses and sharia compliance to halal context in their life. Using a mixed methodological approach with Analytical Network Process with religious leaders, academic and economics experts, local government, and business actors as the participants, it found that the strategies used to develop halal industry are not appropriate due to internal factors such as lack of standardization, branding, and limited human resources, and external ones which are the absence of a roadmap for halal industry and less supports from the government. Improving effective government policies and training human resources are among the strategies that might be applied. However, it also found greater attention among Indonesian Muslim and non-Muslim communities consuming halal products and enjoying halal experiences as their sharia compliance and lifestyle.